Instantaneous channel characteristics and progression factor based collaborative routing - Bhairavi Ramasamy; Gnanou Florence Sudha (Institute of Advanced Engineering and Science, 2022)
Underwater acoustic sensor networks (UWASN) have enormous applications like investigating oceanographic environment, data gathering, scrutiny, calamity avoidance etc. Cooperative communication becomes mandatory when nodes are distributed far apart especially in the ocean environment. The existing relay selection techniques do not consider the instantaneous channel characteristics while selecting the relay nodes. The relays selected based on the outdated channel state information aggravates or worsens the performance of the rapidly changing or dynamic UWASN. Hence, this paper proposes an instantaneous channel characteristics and progression factor (ICPF) based collaborative routing for underwater acoustic sensor networks. It considers numerous indexes such as propagation delay, residual energy, progression factor, spreading, transmission and absorption loss in the forwarding relay node selection. These indexes are averaged and updated periodically to overcome the difficulties caused by the inconsistency and aggressive nature of underwater channel. The progression factor proposed in this work is a prime metric that facilitates efficient data forwarding. Simulation results show that the proposed technique outperforms the existing schemes in terms of packet delivery ratio (PDR), average end to end delay and energy consumption and is capable of achieving PDR of 90.1% for network comprising of 100 acoustic nodes.